A photoelectric sensor with multi-effect coupling enhancement and a method for preparing the same
By using zinc oxide/gold/molybdenum disulfide heterojunction in the photodetector, combined with local plasma resonance and periodic strain effect, the existing photodetectors have solved the problem of narrow detection bands and low response, and achieved high responsiveness and wide band photodetection effects.
Patent Information
- Application Number
- CN202310177623.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Existing single two-dimensional material photodetectors have problems with narrow detection bands and low light response.
The pyroelectric effect enhanced by local plasmon resonance and periodic strain-regulated zinc oxide/gold/molybdenum disulfide heterojunction is adopted to achieve the coupling enhancement of large-area pyroelectric effect and strain effect through physical connection of intermolecular forces.
The photoelectric detection performance is improved, and the photoelectric detection effect with high responsiveness and wide bands is achieved. It also has the advantages of good uniformity, excellent enhancement effect, simple preparation method, low cost and good repeatability.
Smart Images

Figure CN116314392B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectric detection technology, and in particular to a multi-effect coupling enhanced photoelectric sensor and a preparation method thereof. Background Art
[0002] Two-dimensional materials are used in the field of photodetectors, and have advantages over bulk materials such as wide spectrum, sensitivity, and high response. Narrow-bandgap two-dimensional materials and their heterojunctions are the main research objects, such as graphene, black scale (BP), narrow-bandgap TMDS (MoS2, PdSe2, etc.). Since these atomic-thick crystals have strong flexibility and can withstand greater strain than bulk materials, the limit strain of graphene can be around 15%. Studies have shown that in-plane strain and out-of-plane strain can be generated by stretching, compressing or wrinkling two-dimensional materials. The band gap of strained two-dimensional materials can change accordingly. For example, the periodic strain of graphene can open a band gap in samples with intrinsic zero band gap, and the quantum Hall effect has been observed; the strain of MoS2 can convert its indirect band gap into a direct band gap, and reduce the size of the band gap, accelerate the separation of photogenerated carriers, and thus increase the photocurrent.
[0003] As a typical pyroelectric material, zinc oxide not only has the advantages of simple preparation method, chemical stability, non-toxicity, etc., but also has a high specific surface area in its nanostructure. In addition, metal nanoparticles can achieve local surface plasmon resonance under light conditions, enhance the pyroelectric effect of zinc oxide, and increase the pyroelectric current. In the past decade, people have prepared ZnO nanostructures with various morphologies, including nanowires, rods, strips, as well as nano nails, disks, hollow micro-nanotubes, etc. By regulating the corresponding growth process, the ideal morphology can be obtained. For example, a polystyrene (PS) sphere self-assembled colloidal template is used to create a graphic seed layer to guide the growth of zinc oxide nanorod structure. The corresponding array can be obtained by growing ZnO using the above template. However, the colloidal template faces problems such as stability and repeatability during the experiment, which is not conducive to the batch growth of nanorod arrays. The success rate of preparing a large area of small-size hole templates by photolithography is higher, and periodic ZnO nanorod clusters of controllable size can be grown. Nanorod array clusters of different sizes have different strain effects on the wet-transferred MoS2 layer above, and thus have different abilities to regulate the band gap size.
[0004] From the above, it can be seen that in the field of photoelectric detection, strain characteristics can be used to prepare a photoelectric sensor based on controllable strain regulation with low cost, simple process, high uniformity and good enhancement effect.
[0005] It should be noted that the above introduction to the technical background is only for the convenience of providing a clear and complete description of the technical solutions of the present application and for the convenience of understanding by those skilled in the art. It cannot be considered that the above technical solutions are well known to those skilled in the art simply because they are described in the background technology section of the present application. Summary of the invention
[0006] In view of the problems of narrow detection band and low light response of existing single two-dimensional material photodetectors, the present invention provides a multi-effect coupling enhanced photoelectric sensor of zinc oxide / gold / molybdenum disulfide heterojunction based on local plasma resonance enhanced pyroelectric effect and periodic strain regulation and a preparation method thereof. The present invention uses intermolecular force to physically connect and then obtain large-area pyroelectric and strain effect coupling enhanced photoelectric detection performance, and has the advantages of good uniformity, excellent enhancement effect, simple preparation method, low cost, good repeatability, etc.
[0007] In order to achieve the above-mentioned purpose, the present invention provides a multi-effect coupling enhanced photoelectric sensor, the structure of which includes a molybdenum disulfide layer, gold nanoparticles, a glass substrate and a plurality of zinc oxide nanorods, the zinc oxide nanorods standing upright on the glass substrate, the gold nanoparticles attached to the side walls of the zinc oxide nanorods, the molybdenum disulfide layer is arranged on the plurality of zinc oxide nanorods, and is connected to the zinc oxide nanorods through intermolecular forces.
[0008] According to one aspect of the present invention, the plurality of zinc oxide nanorods are a cluster array formed by zinc oxide nanorods.
[0009] According to one aspect of the present invention, the molybdenum disulfide layer is a single layer of molybdenum disulfide.
[0010] According to one aspect of the present invention, the gold nanoparticles are spherical with a diameter of 50 to 100 nm.
[0011] According to one aspect of the present invention, the zinc oxide nanorods are upright hexagonal prisms with an outer diameter of 50-100 nm and a height of 1-2 μm.
[0012] According to one aspect of the present invention, the glass substrate has a size of 1 cm×1 cm and a thickness of 1100 μm.
[0013] Based on the same inventive concept, the present invention also discloses a method for preparing any of the above-mentioned multi-effect coupling enhanced photoelectric sensors, comprising the following steps:
[0014] Step 1: Spin-coat zinc oxide on a glass substrate, and after curing, place it in a box furnace for annealing and orientation at 450-500° C. to obtain a zinc oxide seed layer;
[0015] Step 2: After spin coating the reverse adhesive on the zinc oxide seed layer and baking, the layer is exposed and flood-exposed for a second time, and then immersed in a developer to obtain a seed layer with cavities;
[0016] Step 3: Place the seed layer with holes on the side wall of the reactor liner, facing downward, and undergo a hydrothermal reaction to obtain a plurality of zinc oxide nanorods of a desired size;
[0017] Step 4: Invert and paste a plurality of zinc oxide nanorods of a desired size in a magnetron sputtering Ar gas chamber, sputter a gold film of a certain thickness on the side wall of the zinc oxide nanorods, and anneal to obtain uniformly distributed gold nanoparticles;
[0018] Step 5: Spin-coat an EVA support layer on the molybdenum disulfide layer grown by CVD on the copper foil, bake and shape it to obtain Cu / MoS2 / EVA, put the Cu / MoS2 / EVA into an ammonium persulfate solution to etch Cu, then use filter paper to scoop the MoS2 / EVA into deionized water, and finally scoop it onto the zinc oxide nanorod array to obtain MoS2 / EVA / ZnO;
[0019] Step 6: Soak MoS2 / EVA / ZnO in xylene to dissolve the EVA support layer, and finally wash it with alcohol and deionized water in turn, let it stand and dry, and obtain a multi-effect coupling enhanced photoelectric sensor.
[0020] According to one aspect of the present invention, in step 1, the curing temperature is 80°C; in step 2, the baking temperature is 100°C; in step 3, the hydrothermal reaction is specifically: placing the reactor in a 90°C oven for 2 hours of hydrothermal reaction, and after the reaction is completed, drying at 60°C in vacuum for 2 hours.
[0021] According to one aspect of the present invention, in step 4, the sputtering power is 100 W and the time is 2 min; the thickness of the gold film is 100 nm; the annealing temperature is 350° C.; and the diameter of the gold nanoparticles is 50 to 100 nm.
[0022] According to one aspect of the present invention, step 5 is specifically as follows: cutting the monolayer molybdenum disulfide layer and copper foil grown on the copper foil into a size of 0.5 cm × 0.5 cm, sealing the four sides with tape and sticking them on ordinary glass; preparing EVA solution with vinyl acetate and xylene in a certain proportion, and slowly shaking until evenly mixed; placing the above-mentioned glass sheet in a glue spreader, spin coating a layer of EVA at a speed of 1500 rpm, then removing the tape around it, placing it on a hot table and baking it at 100°C for 10 minutes; placing the baked Cu / MoS2 / EVA vertically in ammonium persulfate; the MoS2 / EVA after etching is transparent, using filter paper to assist in scooping it into deionized water, then using tweezers to gently pick up the target substrate, and slowly scooping it out of the water at an angle of 45°; after standing and drying, gently placing it in xylene and anhydrous ethanol in turn and soaking it for two hours each, finally washing away the organic matter with deionized water, and finally scooping it onto the zinc oxide nanorod array to obtain MoS2 / EVA / ZnO.
[0023] Principle of the present application: The photoelectric sensor of the present invention forms a one-dimensional / two-dimensional heterostructure by compounding a molybdenum disulfide layer with a zinc oxide nanorod height difference substrate; utilizes a photolithography template to control the zinc oxide nanorods to achieve periodic array growth; successively adopts magnetron sputtering and thermal annealing processes to achieve uniform distribution of gold nanoparticles on the zinc oxide nanorods; the monolayer of molybdenum disulfide at the top of the nanorod produces a periodic strain effect, and the band gap of the strained molybdenum disulfide changes, thereby increasing the rate of photogenerated carrier generation; and, based on the pyroelectric effect of zinc oxide, when the temperature of the device changes due to light, a voltage appears at both ends of the material or a current is generated; based on the strain effect of molybdenum disulfide, when an external force causes it to be strained, the band gap will decrease accordingly, and this device design couples the two effects, which helps to improve the responsiveness of photodetection and broaden the band of photodetection. In summary, the structure of the zinc oxide / gold / molybdenum disulfide heterojunction photoelectric sensor based on local plasma resonance enhanced pyroelectric effect and periodic strain regulation provided by the present invention has the advantages of simple preparation method, controllable structure, better uniformity and better stability, and can prepare large-area small-size periodic strain composite structures.
[0024] Beneficial effects of the present invention:
[0025] (1) In the photoelectric sensor of the present invention, the wet transfer process of the molybdenum dioxide layer is different from the traditional PMMA-assisted transfer method. EVA, as an elastic polymer, has better flexibility and stress cracking resistance than PMMA. During the transfer process, EVA is sufficient to assist the molybdenum disulfide in supporting the large external force brought by the columnar zinc oxide, protecting it from damage, and obtaining a large area of high-quality strained molybdenum disulfide.
[0026] (2) In the photoelectric sensor of the present invention, the morphology of the periodic nanorod array cluster is changed by adjusting the aperture and spacing of the mask to achieve different degrees of strain, and the specific strain value can be obtained through physical characterization such as AFM.
[0027] (3) In the photoelectric sensor of the present invention, metal nanoparticles are attached to zinc oxide. When light generates a pyroelectric effect, a spontaneous polarization intensity change (△Ps) occurs, and surface polarization charges are generated in a certain direction of the crystal to obtain a pyroelectric current. Zinc oxide nanorods have a large specific surface area, which can increase the light contact area, and a one-dimensional structure can increase electron mobility. Metal nanoparticles are used to enhance the pyroelectric effect, so that the temperature change brings a larger photocurrent value.
[0028] (4) The method for preparing the photoelectric sensor of the present invention can achieve the manufacturing accuracy of the traditional method.
[0029] (5) The photoelectric sensor of the present invention connects the pyroelectric material and the two-dimensional strain material through intermolecular forces, and cleverly uses microstructures to further improve the performance of the photoelectric detector, thereby preparing a heterojunction photoelectric sensor structure with high response and wide band. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A schematic top view of a ZnO / Au composite structure according to an embodiment of the present invention;
[0031] Figure 2 A schematic top view of the ZnO / Au / MoS2 composite structure according to an embodiment of the present invention;
[0032] Figure 3 A schematic side view of a ZnO / Au / MoS2 composite structure according to an embodiment of the present invention;
[0033] Figure 4 This is a SEM image of the zinc oxide nanorods described in the embodiment of the present invention;
[0034] Figure 5 This is a SEM image of a cluster array formed by zinc oxide nanorods described in an embodiment of the present invention.
[0035] Description of the drawings: 1. Glass substrate; 2. Zinc oxide nanorods; 3. Gold nanoparticles; 4. Molybdenum disulfide layer. DETAILED DESCRIPTION
[0036] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0037] At present, single-layer two-dimensional material photodetectors have problems such as complex preparation and uncontrollable problems, as well as low photoelectric conversion efficiency of single material photodetectors.
[0038] In order to solve the above problems, the present invention provides a photoelectric sensor with multi-effect coupling enhancement, such as Figure 1-3 As shown, the structure of the photoelectric sensor includes a molybdenum disulfide layer 4, gold nanoparticles 3, a glass substrate 1 and a plurality of zinc oxide nanorods 2 to form a ZnO / Au / MoS2 composite structure, the zinc oxide nanorods 2 are upright on the glass substrate 1, the gold nanoparticles 3 are attached to the side walls of the zinc oxide nanorods 2, the molybdenum disulfide layer 4 is arranged on the plurality of zinc oxide nanorods 2, and is connected to the zinc oxide nanorods 2 through intermolecular forces.
[0039] In some embodiments of the present application, the plurality of zinc oxide nanorods are cluster arrays formed by zinc oxide nanorods 2. It should be noted that the cluster array of zinc oxide nanorods causes corresponding periodic strain in molybdenum disulfide, and the strain degree of molybdenum disulfide is adjusted according to the size of the array.
[0040] In some embodiments of the present application, the molybdenum disulfide layer is a single layer of molybdenum disulfide.
[0041] In some embodiments of the present application, the gold nanoparticles are spherical with a diameter of 50-100 nm. It should be noted that the gold nanoparticles are evenly distributed, which is beneficial to enhancing the pyroelectric effect of the zinc oxide nanorods.
[0042] In some embodiments of the present application, Figure 4-5 As shown, the zinc oxide nanorods are upright hexagonal prisms with an outer diameter of 50-100 nm and a height of 1-2 μm.
[0043] In some embodiments of the present application, the glass substrate has a size of 1 cm×1 cm and a thickness of 1100 μm.
[0044] In order to solve the above problems, the present invention provides a method for preparing any of the above-mentioned multi-effect coupling enhanced photoelectric sensors, comprising the following steps:
[0045] Step 1: Spin-coat zinc oxide on a glass substrate, and after curing, place it in a box furnace for annealing and orientation at 450-500° C. to obtain a zinc oxide seed layer;
[0046] It should be noted that the glass substrate is cleaned by ultrasonic cleaning with acetone and alcohol and then dried at high temperature to obtain a clean glass substrate.
[0047] It should be noted that the purpose of annealing at 450-500° C. in a box furnace is to make the zinc oxide nanorods have a better (002) lattice orientation, and the temperature has a great influence on the lattice orientation.
[0048] Step 2: After spin coating the reverse adhesive on the zinc oxide seed layer and baking, the layer is exposed and flood-exposed for a second time, and then immersed in a developer to obtain a seed layer with cavities;
[0049] It should be noted that the exposure intensity needs to be adjusted according to the hole size to ensure that the residual glue in the hole can be removed smoothly.
[0050] Step 3: Place the seed layer with holes on the side wall of the reactor liner, facing downward, and undergo a hydrothermal reaction to obtain a plurality of zinc oxide nanorods of a desired size;
[0051] Step 4: Invert and paste a plurality of zinc oxide nanorods of a desired size in a magnetron sputtering Ar gas chamber, sputter a gold film of a certain thickness on the side wall of the zinc oxide nanorods, and anneal to obtain uniformly distributed gold nanoparticles;
[0052] It should be noted that the purpose of the above annealing is to aggregate the gold film and obtain gold nanoparticles with a size of 50 to 100 nm and uniform distribution on the side walls of the zinc oxide nanorods.
[0053] It should be noted that the thickness of the sputtered gold film determines the size of the nanoparticles.
[0054] Step 5: Spin-coat an EVA support layer on the molybdenum disulfide layer grown by CVD on the copper foil, bake and shape it to obtain Cu / MoS2 / EVA, put the Cu / MoS2 / EVA into an ammonium persulfate solution to etch Cu, then use filter paper to scoop the MoS2 / EVA into deionized water, and finally scoop it onto the zinc oxide nanorod array to obtain MoS2 / EVA / ZnO;
[0055] It should be noted that the EVA support layer is different from the traditional PMMA. It has better flexibility and can transfer molybdenum disulfide to the nanorods without large-scale cracks.
[0056] It should be noted that the above-mentioned single-layer MoS2 transfer method is a wet transfer method.
[0057] Step 6: Soak MoS2 / EVA / ZnO in xylene to dissolve the EVA support layer, and finally wash it with alcohol and deionized water in turn, let it stand and dry, and obtain a multi-effect coupling enhanced photoelectric sensor.
[0058] In some embodiments of the present application, in step 1, the curing temperature is 80°C; in step 2, the baking temperature is 100°C; in step 3, the hydrothermal reaction is specifically: placing the reactor in a 90°C oven for 2 hours of hydrothermal reaction, and after the reaction is completed, drying at 60°C in vacuum for 2 hours.
[0059] In some embodiments of the present application, in step 4, the sputtering power is 100 W, the time is 2 min; the thickness of the gold film is 100 nm; the annealing temperature is 350° C.; and the diameter of the gold nanoparticles is 50 to 100 nm.
[0060] In some embodiments of the present application, step 5 is specifically as follows: the monolayer molybdenum disulfide layer and the copper foil grown on the copper foil are cut into a size of 0.5 cm × 0.5 cm, the four sides are sealed with tape and attached to ordinary glass; vinyl acetate and xylene are mixed into an EVA solution in a certain proportion, and slowly shaken until evenly mixed; the above-mentioned glass sheet is placed in a glue spreader, a layer of EVA is spin-coated at a speed of 1500 rpm, and then the tape around it is removed, and it is placed on a hot stage and baked at 100 ° C for 10 minutes; the baked Cu / MoS2 / EVA is placed vertically in ammonium persulfate; the MoS2 / EVA after etching is transparent, and filter paper is used to assist in scooping it into deionized water, and then the target substrate is gently clamped with tweezers and slowly removed from the water at an angle of 45°; after it is left to dry, it is gently placed in xylene and anhydrous ethanol in turn and soaked for two hours each, and finally the organic matter is washed away with deionized water, and finally it is scooped onto the zinc oxide nanorod array to obtain MoS2 / EVA / ZnO.
[0061] In some embodiments of the present application, in step 1, the zinc oxide is spin-coated for no less than 7 times to obtain a thicker and more uniform zinc oxide seed layer.
[0062] In some embodiments of the present application, in step 2, the baking device used for baking is a hot stage, and the exposure intensity is adjusted accordingly according to the thickness of the photoresist.
[0063] In some embodiments of the present application, in step 3, the temperature error of the hydrothermal reaction is controlled within 0.5°C, and the time error of the hydrothermal reaction is controlled within 10 minutes.
[0064] Example 1
[0065] A method for preparing a multi-effect coupling enhanced photoelectric sensor:
[0066] (1) 1 cm × 1 cm glass sheet with a thickness of 1100 μm as substrate; (2) Copper foil CVD growth of a single layer of molybdenum disulfide; (3) Xylene solution, acetone solution, anhydrous ethanol, deionized water; (4) Zinc acetate dihydrate powder, zinc nitrate hexahydrate powder, ethanolamine solution, polyethyleneimine solution, hexamethylenetetramine powder, ammonium persulfate powder, vinyl acetate solution; (5) AZ6112 photoresist and developer; (6) High-purity gold target.
[0067] The specific steps are as follows:
[0068] Step 1: Clean the glass:
[0069] Take a 1cm×1cm, 1100μm thick ordinary quartz glass sheet, ultrasonically clean it in acetone solution, anhydrous ethanol and deionized water for 480 seconds, then blow dry it with nitrogen, and then bake it on a hot plate at 80℃ for 5 minutes, and finally let the glass sheet cool naturally at room temperature;
[0070] Step 2: Prepare the seed layer:
[0071] Prepare a ZnO seed layer solution, use 30 mL of anhydrous ethanol as a solvent, prepare 0.3 mol / L zinc acetate dihydrate, add 0.3 mol / L ethanolamine as a complexing agent, seal with a sealing film, heat to 40°C and stir magnetically until completely dissolved, and let stand at room temperature for 12 hours; put the glass piece cleaned and dried in step 1 on the stage of a glue spreader, use a pipette to absorb 50 μL of the seed layer solution at a time, and evenly drip it on the glass piece, and set the glue spreader to a single speed of 4000 rpm for 20 seconds; repeat the above spin coating steps 10 to 12 times; place the spin-coated glass piece on a hot plate and heat and cure at 80°C for 10 minutes; put the cured glass piece in a box furnace and calcine at 500°C for 30 minutes for orientation.
[0072] Step 3: Prepare the mask:
[0073] The glass slide with the seed layer prepared was placed in a coater and spin-coated with a layer of AZ6112 (reverse adhesive) and then pre-baked on a hot stage at 100°C for 1 min; exposed in a photolithography machine (exposure, secondary flooding), immersed in the developer for 1 min, and finally washed in deionized water and dried naturally to obtain a seed layer with an array template.
[0074] Step 4: Hydrothermal growth of ZnO nanorods:
[0075] Use 30mL of deionized water as solvent, take 0.003mol / L polyethyleneimine, 0.05mol / L zinc nitrate hexahydrate and 0.05mol / L hexamethylenetetramine, seal with sealing film, heat at 40℃ and stir magnetically for 1h; place the glass piece obliquely downward against the side wall of the reactor, add the prepared solution, put it in an oven and react at 90℃ for 2h; after the hydrothermal reaction is completed, take out the glass piece, put it in deionized water to wash away the precipitate, and vacuum dry it at 60℃ for 1h.
[0076] Step 5: Synthesis of gold nanoparticles:
[0077] The zinc oxide nanorods obtained above were placed upside down in the magnetron sputtering chamber, and vacuum was drawn by mechanical pump and molecular pump successively. When the pressure was less than 2.4×10-3Pa, Ar gas was introduced, and the sputtering power supply was turned on. When the power was stable at about 100W, the gold target was ignited and sputtered for 1min, then the sputtering power supply was turned off, the Ar gas was turned off, nitrogen gas was introduced to make the internal and external pressures consistent, and the wafer was taken out. The sputtered wafer was placed in a box furnace, and the temperature was raised stepwise, and kept at 350℃ for 1h, so that the gold film was agglomerated, and the gold nanoparticles with uniform distribution and similar size were attached to the zinc oxide nanorods. After the box furnace was cooled to room temperature, the wafer was taken out.
[0078] Step 6: Wet transfer of molybdenum disulfide:
[0079] The molybdenum disulfide grown on the copper foil by CVD was cut into a size of 0.5cm×0.5cm, and the edges were sealed with tape and attached to the smooth glass; vinyl acetate and xylene were prepared in a concentration of 1:4, and 50μL was taken by a pipette and dropped on the molybdenum disulfide. The spin coating parameter of the glue spreader was 1500rpm30s, and the tape was removed and baked at 130℃ for 10min; the baked Cu / MoS2 / EVA was placed vertically in an ammonium persulfate solution with a concentration of 6.25wt%; it was allowed to soak for about 4h to prevent the molybdenum disulfide from breaking when the surrounding vibrates; the MoS2 / EVA after removing the copper foil was transparent, and the filter paper was cut into small squares, placed in the ammonium persulfate solution at a 45° angle, and the MoS2 / EVA was slowly fished out and slowly placed in deionized water.
[0080] Step 7: Obtain strained MoS2 / Au / ZnO nanorods and make photosensor structures:
[0081] Place the substrate obtained in step 4 into the deionized water of step 5, slowly scoop MoS2 / EVA onto the ZnO nanorod array cluster at an angle of 45°, and dry it naturally; the dried sheet is slowly placed in xylene and soaked for 2 hours, and then slowly placed in anhydrous ethanol and soaked for 2 hours to remove the surface EVA, and then placed in deionized water for cleaning and naturally dried to obtain a strained molybdenum disulfide / zinc oxide nanorod composite photoelectric sensor structure.
[0082] The implementation advantages of the present invention are:
[0083] (1) In the photoelectric sensor of the present invention, the wet transfer process of the molybdenum dioxide layer is different from the traditional PMMA-assisted transfer method. EVA, as an elastic polymer, has better flexibility and stress cracking resistance than PMMA. During the transfer process, EVA is sufficient to assist the molybdenum disulfide in supporting the large external force brought by the columnar zinc oxide, protecting it from damage, and obtaining a large area of high-quality strained molybdenum disulfide.
[0084] (2) In the photoelectric sensor of the present invention, the morphology of the periodic nanorod array cluster is changed by adjusting the aperture and spacing of the mask to achieve different degrees of strain, and the specific strain value can be obtained through physical characterization such as AFM.
[0085] (3) In the photoelectric sensor of the present invention, metal nanoparticles are attached to zinc oxide. When light generates a pyroelectric effect, a spontaneous polarization intensity change (△Ps) occurs, and surface polarization charges are generated in a certain direction of the crystal to obtain a pyroelectric current. Zinc oxide nanorods have a large specific surface area, which can increase the light contact area, and a one-dimensional structure can increase electron mobility. Metal nanoparticles are used to enhance the pyroelectric effect, so that the temperature change brings a larger photocurrent value.
[0086] (4) The method for preparing the photoelectric sensor of the present invention can achieve the manufacturing accuracy of the traditional method.
[0087] (5) The photoelectric sensor of the present invention connects the pyroelectric material and the two-dimensional strain material through intermolecular forces, and cleverly uses microstructures to further improve the performance of the photoelectric detector, thereby preparing a heterojunction photoelectric sensor structure with high response and wide band.
[0088] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A multi-effect coupling enhanced photoelectric sensor, characterized in that: The structure of the photoelectric sensor includes a molybdenum disulfide layer, gold nanoparticles, a glass substrate and a plurality of zinc oxide nanorods, wherein the zinc oxide nanorods stand upright on the glass substrate, the gold nanoparticles are attached to the side walls of the zinc oxide nanorods, and the molybdenum disulfide layer is arranged on the plurality of zinc oxide nanorods and is connected to the zinc oxide nanorods through intermolecular forces.
2. The multi-effect coupling enhanced photoelectric sensor according to claim 1, characterized in that: The plurality of zinc oxide nanorods are a cluster array formed by zinc oxide nanorods.
3. The multi-effect coupling enhanced photoelectric sensor according to claim 1, characterized in that: The molybdenum disulfide layer is a single layer of molybdenum disulfide.
4. The multi-effect coupling enhanced photoelectric sensor according to claim 1, characterized in that: The gold nanoparticles are spherical and have a diameter of 50 to 100 nm.
5. The multi-effect coupling enhanced photoelectric sensor according to claim 2, characterized in that: The zinc oxide nanorods are upright hexagonal prisms with an outer diameter of 50-100 nm and a height of 1-2 μm.
6. The multi-effect coupling enhanced photoelectric sensor according to claim 1, characterized in that: The glass substrate has a size of 1 cm×1 cm and a thickness of 1100 μm.
7. A method for preparing a multi-effect coupling enhanced photoelectric sensor according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Spin-coat zinc oxide on a glass substrate, and after curing, place it in a box furnace for annealing and orientation at 450-500° C. to obtain a zinc oxide seed layer; Step 2: After spin coating the reverse adhesive on the zinc oxide seed layer and baking, the layer is exposed and flood-exposed for a second time, and then immersed in a developer to obtain a seed layer with cavities; Step 3: Place the seed layer with holes on the side wall of the reactor liner, facing downward, and undergo a hydrothermal reaction to obtain a plurality of zinc oxide nanorods of a desired size; Step 4: Invert and paste a plurality of zinc oxide nanorods of a desired size in a magnetron sputtering Ar gas chamber, sputter a gold film of a certain thickness on the side wall of the zinc oxide nanorods, and anneal to obtain uniformly distributed gold nanoparticles; Step 5: Spin-coat an EVA support layer on the molybdenum disulfide layer grown by CVD on the copper foil, bake and shape it to obtain Cu / MoS2 / EVA, put the Cu / MoS2 / EVA into an ammonium persulfate solution to etch Cu, then use filter paper to scoop the MoS2 / EVA into deionized water, and finally scoop it onto the zinc oxide nanorod array to obtain MoS2 / EVA / ZnO; Step 6: Soak MoS2 / EVA / ZnO in xylene to dissolve the EVA support layer, and finally wash it with alcohol and deionized water in turn, let it stand and dry, and obtain a multi-effect coupling enhanced photoelectric sensor.
8. The method for preparing the multi-effect coupling enhanced photoelectric sensor according to claim 7, characterized in that: In step 1, the curing temperature is 80°C; in step 2, the baking temperature is 100°C; in step 3, the hydrothermal reaction is specifically: placing the reactor in a 90°C oven for 2 hours of hydrothermal reaction, and after the reaction is completed, drying at 60°C in vacuum for 2 hours.
9. The method for preparing the multi-effect coupling enhanced photoelectric sensor according to claim 7, characterized in that: In step 4, the sputtering power is 100 W and the time is 2 min; the thickness of the gold film is 100 nm; the annealing temperature is 350° C.; and the diameter of the gold nanoparticles is 50 to 100 nm.
10. The method for preparing a multi-effect coupling enhanced photoelectric sensor according to claim 7, characterized in that: The step 5 is specifically as follows: the monolayer molybdenum disulfide layer and the copper foil grown on the copper foil are cut into a size of 0.5 cm×0.5 cm, the four sides are sealed with tape and attached to ordinary glass; vinyl acetate and xylene are mixed into an EVA solution according to a certain ratio, and slowly shaken until evenly mixed; the above-mentioned glass sheet is placed in a glue spreader, a layer of EVA is spin-coated at a speed of 1500 rpm, and then the tape around it is removed, and it is placed on a hot plate and baked at 100°C for 10 minutes; the baked Cu / MoS2 / EVA is placed vertically in ammonium persulfate; the MoS2 / EVA after etching is transparent, and it is scooped into deionized water with the help of filter paper, and then the target substrate is gently clamped with tweezers and slowly removed from the water at an angle of 45°; after it is left to stand and dry, it is gently placed in xylene and anhydrous ethanol in turn and soaked for two hours each, and finally the organic matter is washed off with deionized water, and finally it is scooped onto the zinc oxide nanorod array to obtain MoS2 / EVA / ZnO.
Citation Information
Patent Citations
Nano-wire tunneling field-effect transistor with vertical structure and preparation method thereof
CN102412301A
Ultraviolet / red light dual-band light detector and preparation method thereof
CN106505112A